PROJETO DE CONTROLADOR ROBUSTO VIA OTIMIZAÇÃO CONVEXA - Souza, Valeska Martins de (2002)
In this dissertation a new methodology of based convex optimization in linear matrix inaqualities is proposal as basic instrument for the synthesis of robust controllers of discrete and linear dynamic systems that take care of to the specifications of perturbations of worse case.